Microbiological and Physicochemical Quality of Carp sausage Enriched With Propolis Natural Extract during Chilled Storage - Coban, Mehmet Zulfu; Coban, Ozlem Emir; Fadiloglu, Eylem Ezgi (Taylor & Francis Inc, 2019)
This study aimed to determine the effect of propolis extract on quality of liquid smoked carp (Cyprinus carpio) sausage stored at 2 degrees C for 9 weeks. Carp sausages were separated into three groups: control group, without propolis extract; second group, with 1% (w/w) propolis extract added; and third group, with 2% (w/w) propolis extract added. Propolis extract added carp sausages showed lower total volatile basic nitrogen (TVB-N) value, peroxide value (PV), and free fatty acid (FFA) content compared to control during the storage period. During 9 weeks of storage, propolis extract added carp sausages showed significantly lower total aerobic mesophilic bacteria (TAMB) and psychrophilic bacteria count (PBC) than those of control samples (p < .05). Yeast and mold were not detected in all fish sausages throughout the storage period.
Keywords: Common carp (C; carpio); liquid smoked fish sausage; propolis; quality